Aminoquinoline-Based Tridentate (NNN)-Copper Catalyst for C–N Bond-Forming Reactions from Aniline and Diazo Compounds - Mohsen Teimouri; Selvam Raju; Edward Acheampong; Allison N. Schmittou; Bruno Donnadieu; David O. Wipf; Brad S. Pierce; Sean L. Stokes; Joseph P. Emerson (Molecules, 2024)
A new tridentate Cu2+ complex based on (E)-1-(pyridin-2-yl)-N-(quinolin-8-yl)methanimine (PQM) was generated and characterized to support the activation of diazo compounds for the formation of new C–N bonds. This neutral Schiff base ligand was structurally characterized to coordinate with copper(II) in an equatorial fashion, yielding a distorted octahedral complex. Upon characterization, this copper(II) complex was used to catalyze an efficient and cost-effective protocol for C–N bond formation between N-nucleophiles and copper carbene complexes arising from the activation of diazo carbonyl compounds. A substrate scope of approximately 15 different amine-based substrates was screened, yielding 2° or 3° amine products with acceptable to good yields under mild reaction conditions. Reactivity towards phenol and thiophenol were also screened, showing relatively weak C–O or C–S bond formation under optimized conditions.